Extraction d'ADN et effet antimicrobien de l’extrait de fourmis (Genre, Camponotus) - MAMMERI, Khadidja Aicha; BRAHAMI, Yassamine (My University, 2023)
This work covers two intriguing aspects of ants: extraction of their DNA, and the exploration of the natural antimicrobial properties of their extracts. We first collected the ants from the forest of Khadra Mostaganem. To carry out the extraction of the DNA, we did the following steps: A mechanical rupture of the ants’ cells, chemical rupture, and DNA precipitation. The DNA sample was loaded onto an agarose gel and subsequently subjected to electrophoresis. Finally, the agarose gel was viewed under a UV light. Additionally, we made two extracts from ants, an aqueous extract, and a methanolic extract, then we tested their antimicrobial potential on E coli, and pseudomonas strains. The DNA extraction process was successful, but the DNA extracted is not pure. The antibiogram results demonstrate a weak antimicrobial effect of ant extracts on E. coli and no effect on pseudomonads. Perspectives: the DNA extraction methods we used, is simple and can yield results. Despite initial promise, ant extracts may not represent an optimal solution in combating bacterial pathogens, warranting further exploration of alternative avenues for antimicrobial research.
Keywords: Ants; DNA extraction; electrophoresis; antimicrobial properties; aqueous extract; methanolic extract